Bacteriospermia and Sperm Quality of Cryopreserved Bull Semen Used in Artificial Insemination of Cows in South Wollo Zone, Ethiopia - Abadi Amare Reda; Gizat Almaw; Solomon Abreha; Wedajo Tadeg; Belege Tadesse (Veterinary Medicine International)
The objectives of this trial were to estimate prevalence of bacteriospermia, to determine the bacterial load, and to isolate the types of bacteria as well as to assess the association between bacterial load and sperm quality traits in cryopreserved bull semen in field conditions in the South Wollo Zone. A total of 309 cryopreserved straws of semen from the Holstein Friesian (HF)-cross bull (n = 180 straws) and pure Jersey bull (n = 129 straws) were investigated. Bacteriological assessments of the presence of aerobic bacteria, estimation of bacterial count and bacterial isolation, as well as semen quality were performed. Aerobic bacterial contamination was prevalent in 38.8% of the semen straws. No significant difference in the prevalence of bacteriospermia was observed among bulls although the HF-cross bull had a higher prevalence (40.0%). But, significant difference in prevalence of bacteriospermia was found among semen ejaculates of the same bull. The risk of bacteriospermia in the HF-cross bull was higher (Odds ratio = 1.86, 95% CI = 0.168–20.26) compared to Jersey although not significant. Overall average bacterial load of 50.38 ± 16.29 colony-forming units (CFU)/ml (from nil to 1318.20 CFU/ml) was found. No significant difference in bacterial count among bulls and their ejaculates was observed. Moreover, correlation analysis revealed that the proportions of motility, live, and normal morphology were negatively influenced by an increase in the bacterial contamination of semen. In this study, three isolates of coagualse-negative Staphylococcus species and one isolate of Corynebacterium species were found. Average percentages of sperm motility (48.35 ± 1.23), live (66.08 ± 1.0), and normal morphology (80.62 ± 1.24) were observed. It was concluded that cryopreservation does not guarantee the quality of semen from bacterial contamination. Hence, meticulous care should be adopted to prevent contamination of semen by bacteria during collection, transportation, processing, and storage times.